PENERAPAN KOMPRES ALLIUM CEPA L.VAR TERHADAP PENURUNANHIPERTERMIA PADA PASIEN HIPERPIREKSIA DI RUANGANINSTALASI GAWAT DARURAT RS. TK II PELAMONIA - Asriati Asriati; Ernasari Ernasari; Muhajirin Muhajirin; Rochfika Rochfika (CV. ADIBA AISHA AMIRA, 2025)
Hyperthermia is a condition where body temperature rises above normal due to a disruption in thermoregulatory mechanisms, where heat production exceeds the body's ability to dissipate heat. In children, hyperthermia accompanied by hyperprexia can lead to serious complications such as seizures, dehydration, and even impaired consciousness. Hyperthermia can be managed through pharmacological and non-pharmacological therapies. One such non-pharmacological intervention is a red onion compress, which is traditionally believed to be effective in lowering body temperature. Objective: This study aims to determine the effectiveness of red onion compresses in reducing hyperthermia in patients with hyperprexia and to analyze its role as an innovation in evidence-based practice-based nursing care. Methods: This study used a case study approach on a 4-year-old child with a body temperature of 41.9℃. Intervention was carried out through a 10-minute compress of 3 cloves of red onion combined with standard nursing measures such as vital sign monitoring, fluid administration, family education, and collaborative antipyretic administration. Data were collected through clinical observation, family interviews, and nursing care documentation. Results: After the intervention, the patient's body temperature dropped from 41.9℃ to 37.9℃, the patient no longer shivered, the face looked fresher, the lip mucosa began to moisten, and complaints of nausea and vomiting decreased. Conclusion: Onion compresses have been proven to be effective in helping to reduce body temperature in patients with hyperthermia. This intervention can be used as a simple, safe, and supportive non-pharmacological therapy that can be used in conjunction with medical therapy. Suggestion: For hospitals, it is hoped that onion compress interventions can be considered for inclusion in the Nursing Standard Operating Procedure (SOP) as an alternative non-pharmacological action. For the development of nursing science, further research with a larger sample size is needed to strengthen the scientific evidence of the effectiveness of onion compresses in managing hyperthermia.